Produtividade do milho safrinha e modificações químicas de um latossolo em sistema plantio direto em função de espécies de cobertura após calagem superficial - Andreotti, Marcelo [UNESP]; Araldi, Marcelo; Guimaraes, Vandeir Francisco; Furlani Junior, Enes [UNESP]; Buzetti, Salatier [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
Modern agriculture is undergoing profound changes, with demands for more efficient management practices in the production systems used in each area. The objectives of this study were: to evaluate the effect of different covering species on a no-tillage system; to find the results of lime application on soil surface after sowing those forage species; measure the effects on soil chemical properties and subsequent effect on corn yield; and to determine the dry matter produced by each species used. The experiment was conducted on November, 2002, in the town of Palotina, Parana State, Brazil. A randomized block design was used, with 4 repetitions, in a 2x6 factorial scheme -two depths of soil sampling (0-10 and 10-20 cm) and six types of forage covering on the soil (Mucuna deeringiana, Crotalaria juncea, Setaria incana, Pennisetum glancum and Eleusine gracilis, as well as a mix of all these species). 3 t ha(-1) of dolomitic limestone were applied in total surface area, without amending. The covering species associated with the surface limestone application showed improvement in soil fertility, mainly in the layer of 10-20 cm, with prominence to Elensine gracilis, Crotalaria juncea and Setaria incana. Eleusine gracilis and Crotalaria juncea featured the largest dry matter production; however, the great amount of straw of Eleusine gracilis damaged the productivity of corn. Grain and corn straw productivity was higher when previously cultivated along with Setaria incana and the mix of forage species covering.
Winter corn yield and chemical modifications in latosol as a function of covering species after lime application under no-tillage system
Keywords: green manure; forage species; nutrient contents; Zea mays